1991
DOI: 10.1159/000153968
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Glucose-6-Phosphate Dehydrogenase Variants in the Sudan &ndash; Including Gd<sup>Khartoum</sup>, a Hyperactive Slow Variant

Abstract: Erythrocyte glucose-6-phosphate dehydrogenase (G6PD) was characterized in blood samples of 94 male subjects in Sudan having deficient and non-deficient electrophoretic variants. They comprised 44 GdB, 17 GdA, 19 GdB-, 11 GdA- and 3 non-deficient (GdKhartoum) variants. Biochemical characteristics including enzyme activity, electrophoretic mobility, Km for glucose-6-phosphate (G6P) and nicotinamide adenine dinucleotide phosphate (NADP), heat stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…This 348 Socmant ri/Saha/Saha/T ay G6PD Deficiency in Java Table 3. Distribution of G6PD mutations in the G6PD-defïcient Javanese may be similar to GdKharloum, first described in the Sudan and later observed in Saudi Ara bia [25].…”
Section: G6pd Variantssupporting
confidence: 58%
“…This 348 Socmant ri/Saha/Saha/T ay G6PD Deficiency in Java Table 3. Distribution of G6PD mutations in the G6PD-defïcient Javanese may be similar to GdKharloum, first described in the Sudan and later observed in Saudi Ara bia [25].…”
Section: G6pd Variantssupporting
confidence: 58%
“…The other characteristics (Kin G6P), utilization of analogues (2dG6P, dAmNADP), heat stability and pH optimum were within normal range while Km for NADP (23 t~M) and ~ utilization for Gal6P were higher (11~) than that in Gd B. Gd singap~ is a new non-deficient variant unreported in the literature. Recently a new hyper-active variant (Gd Kh~rt~ of slow mobility, prevalent in Sudan and Saudi Arabia has been characterized (Saha and Samuel, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…However, most of the studies have been carried out on G6PD deficient samples because of the ease of screening the test. Population genetics of red cell G6PD in African and Asian populations suggest that the prevalence of non-deficient alleles is not uncommon (Nakatsuji and Miwa, 1979;Samuel et al, 1981;Saha, 1984;Panich, 1986;Saha and Samuel, 1991). As such, probably the earlier studies based on the enzyme deficient samples grossly underestimate the degree of genetic heterogeneity of the Gd locus in man.…”
Section: Introductionmentioning
confidence: 99%
“…Testing with the CareStart POC test provided a higher estimated prevalence, which is consistent with other studies [ 35 38 ]. Earlier reports of G6PD in Sudan focused on enzyme isoforms only, but did not provide associated frequencies [ 6 , 39 ]; and a recent study conducted in Northern Sudan reported on polymorphic genetic variants of the enzyme [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…vivax infection. To date, reports originating from Sudan on glucose-6-phosphate dehydrogenase deficiency (G6PDd) are limited [ 4 6 ]. The G6PD gene consists of 13 exons and 12 introns, which are located on the long arm of the X-chromosome at gene loci Xq28.…”
Section: Introductionmentioning
confidence: 99%